Analysis of the Application of PP No. 71 of 2010 concerning Accrual-Based Government Accounting Standards in the Presentation of Financial Statements at the Kalidoni Sub-District Office, Palembang City - Diah Septa Ameliyati; Andini Utari Putri; Muhammad Hamdan Sayadi (International Journal of Community Service & Engagement, 2023)
This study aims to describe and analyze the presentation of financial statements at the Kalidoni Subdistrict Office of Palembang whether or not it is by the application of PP No. 71 of 2010 concerning Accrual-Based Government Accounting Standards. Data collection techniques used in this study were observation, literature study, interviews, documentation. The data sources were primary and secondary. The results show that the presentation of financial statements at the Kalidoni Sub-district Office of Palembang is by Government Regulation Number 71 of 2010 concerning Accrual-Based Government Accounting Standards. The results of this study are expected to provide benefits for the Kalidoni sub-district office of Palembang.